Chapter Evolution of the surface roughness of a coarse sand after a beach nourishment - López, Isabel (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Research on the evolution of the surface roughness of coarse sand particles that were dumped in January 2020 at Los Locos beach in Torrevieja (Alicante, Spain) is conducted. This sample came from a quarry and presented a high angularity and roughness on the surface of its particles. After a year and a half of dumping the quarry material on the beach, a high degree of decrease in the roughness of the particles is observed; however, to reach the degree of polishing that the particles of a natural beach have, a longer period is necessary.